Effects of supplemental xylanase on in vitro disappearance of dry matter in feed ingredients for swine - Jo, Hyunwoong; Sung, Jung Yeol; Kim, Beob Gyun (Revista Colombiana de Ciencias Pecuarias, 2021)
Background: Alternative feed ingredients are widely used in swine diets to lower feed costs, but these ingredients contain a large quantity of non-starch polysaccharides. Supplemental xylanase is known to break down non-starch polysaccharides. However, the effects of exogenous xylanase from Bacillus subtilis on various feed ingredients have rarely been compared. Objective: To evaluate the effects of supplemental xylanase on in vitro disappearance of dry matter (DM) in various feed ingredients for pigs. Methods: Nine feed ingredients were used to measure in vitro ileal disappearance and in vitro total tract disappearance of DM. Each ground ingredient was supplemented with either supplemental xylanase (9,000 U/g) or cornstarch at 1.0%. Results: Supplemental xylanase increased in vitro ileal disappearance of DM in wheat, barley, wheat flour, and wheat bran (p<0.05). The in vitro total tract disappearance of DM for barley and wheat bran increased with xylanase addition (p<0.05). Conclusion: Exogenous xylanase could increase in vitro ileal DM disappearance in barley, wheat, wheat flour, and wheat bran, but did not affect in vitro total tract DM disappearance in wheat and wheat flour.